Teaching collaborative problem-solving skills to law students - Ryan, Philippa (Law teacher, 2017)
This article describes and critically evaluates a collaborative dispute resolution activity conducted in a mid-degree law subject at an Australian university. Australian law degrees are required to be vocational. Teaching problem-solving to law students is an effective way to impart key professional skills. However, it requires planning and preparation. It is therefore important to reflect on whether the aims of the activity have been achieved. In particular, three ideas about what constitutes good teaching are explored. The first is that good teachers do not simply deliver content - they give their students problems to solve. The second is the expectation employers have that law graduates will readily collaborate with their colleagues. Finally, giving students an opportunity to reflect on what they have learned will enable students to transfer what they have understood and articulated to legal practice. By delineating each of these three teaching aims, it is possible to assess the value and effectiveness of the problem-solving activity. This paper also reflects on the positive impact that is achieved when authentic and ethical legal processes are embedded into student-centred learning.